2006
DOI: 10.1158/1535-7163.mct-05-0203
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant epoetins do not stimulate tumor growth in erythropoietin receptor–positive breast carcinoma models

Abstract: We investigated the significance of erythropoietin receptor (EPOR) expression following treatment with recombinant human erythropoietin (rHuEPO; epoetin A) and the effect of recombinant epoetins (epoetin A, epoetin B, and darbepoetin A) alone or in combination with anticancer therapy on tumor growth in two well-established preclinical models of breast carcinoma (MDA-MB-231 and MCF-7 cell lines). Expression and localization of EPOR under hypoxic and normoxic conditions in MDA-MB-231 and MCF-7 cells were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
57
2
7

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 45 publications
13
57
2
7
Order By: Relevance
“…Furthermore, a number of other studies have shown that EPO does not stimulate tumor growth in vitro or in vivo. Recombinant EPO did not stimulate tumor growth in xenografted mouse tumors [35] and potentiated the positive effects of radiation therapy [36]. Retrospective studies also showed that recombinant EPO prolonged survival in myelodysplastic syndrome (MDS) patients and did not accelerate leukemic transformation [37].…”
Section: Tumor Progression Resulting From Stimulation Of Tumor Cell Ementioning
confidence: 99%
“…Furthermore, a number of other studies have shown that EPO does not stimulate tumor growth in vitro or in vivo. Recombinant EPO did not stimulate tumor growth in xenografted mouse tumors [35] and potentiated the positive effects of radiation therapy [36]. Retrospective studies also showed that recombinant EPO prolonged survival in myelodysplastic syndrome (MDS) patients and did not accelerate leukemic transformation [37].…”
Section: Tumor Progression Resulting From Stimulation Of Tumor Cell Ementioning
confidence: 99%
“…The biological effects of Epo stimulation of tumor cells is still debated with reports of enhanced survival (8,11), proliferation (4,6,(38)(39)(40), resistance to treatment (38,41,42), tumor angiogenesis (43)(44)(45), chemotaxis (46), invasion (47)(48)(49)(50), and migration (40,46,51). Others have reported no discernible effects of Epo (52).…”
Section: Discussionmentioning
confidence: 99%
“…[25][26] Indeed, EPOR activation has been observed in the absence of any modification in growth rate. 27 It may be that EPO-EPOR signaling effects on proliferative and anti-apoptotic pathways are dependent on the biochemical context of each cellular model and therefore must be assessed independently.…”
Section: Discussionmentioning
confidence: 99%